An Investigation of the Bacterial Influence of Acidithiobacillus Thiooxidans on Concrete Composites - Harbulakova Vlasta Ondrejka; Estokova Adriana; Luptakova Alena (E3S Web of Conferences, 2018)
Vegetation and microorganisms present the biological factors that deteriorate concrete. These problems are very visible in places like sewage, underground and hydraulic structures, chemical plants, industrial structures, liquid-containing structures, agricultural structures or marine environments. The most significant biodeteriogens are the sulphur-oxidising bacteria Acidithiobacillus thiooxidans (A. thiooxidans) and the sulphatereducing bacteria (Desulfovibrio spp.) that are responsible for the so-called sulphuretum consortium. Microorganisms that produce sulphuric acid accelerate the deterioration of concrete sewer pipes in a process termed Microbially Induced Concrete Corrosion (MIC). The paper considers the assessment of the release of calcium and silicon from concrete composites with and without coal fly ash by sulphur-oxidizing bacteria. The concrete mixture contained coal fly ash as 5 wt. % and wt. 10 % cement replacement. Prepared composites were exposed to an aggressive microbial environment under laboratory conditions for 3 months. The pH values were measured and studied during this time period. A different resistance against MIC was observed for the concrete composites of different compositions. The highest amount of calcium leached-out from the concrete was in the case of the composites where 10 % cement was replaced by fly ash.